Erratum: Members' Percieved Benefits and Values of the Association for International Agricultural and Extension Education - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Garrett, R., Balinas, M., Wingenbach, G., Rutherford, T., Fath, K., Alvis, S., Bielecki, C., McGucken, A., & Pratt, O. (2014). Members' Percieved Benefits and Values of the Association for International Agricultural and Extension Education. Journal of International Agricultural and Extension Education, 21(2), 6-16” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1228